2010
DOI: 10.2105/ajph.2009.180869
|View full text |Cite
|
Sign up to set email alerts
|

Policy and System Change and Community Coalitions: Outcomes From Allies Against Asthma

Abstract: Community coalitions can successfully achieve asthma policy and system changes and improve health outcomes. Increased core and ongoing community stakeholder participation rather than a higher overall number of participants was associated with more change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 63 publications
0
87
0
Order By: Relevance
“…12 Over the past two decades, evidence supporting the potential benefi ts of CHWs in the USA setting has grown, on the basis of a multitude of pilot programmes, particularly for mental health and chronic diseases (ie, depression, 13 diabetes, [14][15][16][17] hypertension, 18 asthma, 19,20 and cardiovascular disease). 18,21 Expanded CHW programmes are likely to be included in the present round of health-care reform.…”
Section: -4mentioning
confidence: 99%
“…12 Over the past two decades, evidence supporting the potential benefi ts of CHWs in the USA setting has grown, on the basis of a multitude of pilot programmes, particularly for mental health and chronic diseases (ie, depression, 13 diabetes, [14][15][16][17] hypertension, 18 asthma, 19,20 and cardiovascular disease). 18,21 Expanded CHW programmes are likely to be included in the present round of health-care reform.…”
Section: -4mentioning
confidence: 99%
“…7,[16][17][18] The adaptation of the interventions was guided by the conceptual model shown in Fig 1 that draws on structural, process, and outcome components first defined by Donabedian and applied here in the context of a community-based intervention. 17,18 Structural core elements include the material resources, characteristics of the physical/socialorganizational setting, and the number and qualifications of staff.…”
Section: Formative Work and Conceptual Frameworkmentioning
confidence: 99%
“…6 Recognizing that there are multiple reasons why asthma evidence-based care is not being implemented in poor and minority communities, several national grant-funded initiatives have worked toward reducing this gap. [7][8][9] Under the rubric of implementation science and/or translational research, 10,11 some of these efforts seek to create knowledge about the uptake and adaptation of evidence-based practices in "real world" settings. For example, translational research efforts seek to answer questions such as: What adaptations of evidence-based interventions were successful, in what environments, and why?…”
mentioning
confidence: 99%
“…Recent evidence has shown that collaborative community-wide approaches to enhancing health care delivery can generate far-reaching policy and system changes and improvements in health status. 8 To support evidence-based means to reduce inequity in health status, the Alliance to Reduce Disparities in Diabetes was launched by the Merck Company Foundation in 2009. The foundation is providing up to $2 million over 5 years (2009)(2010)(2011)(2012)(2013) to each of the five Alliance sites.…”
Section: 3mentioning
confidence: 99%
“…Each element of the Alliance effort has been shown in carefully evaluated studies to enhance care delivery and health outcomes. 8 Each, however, must be modified to fit the new situation, population, and location.…”
Section: Alliance Principles and Strategiesmentioning
confidence: 99%